2009
DOI: 10.1177/1065912909333132
|View full text |Cite
|
Sign up to set email alerts
|

Morality, Equality, or Locality: Analyzing the Determinants of Support for Same-sex Marriage

Abstract: In this article, the authors develop a model in which they depict individuals' support for same-sex marriage as a function of several clusters of independent variables, including symbolic politics, moral and religious attitudes and attachments, feelings toward gays and lesbians, women's rights and gender roles, concern for minority and civil rights, demographic attributes, and the local context. Using data from the 2004 American National Election Studies survey and the U.S. Census, the authors find that attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 30 publications
1
32
0
1
Order By: Relevance
“…Religious affiliation, Biblical literalism, and church attendance are strong predictors of intolerance toward gays and lesbians (Burdette et al, 2005;Finlay and Walther, 2003) and weaker support for gay rights, particularly same-sex marriage (Gaines and Garand, 2010;Olson et al, 2006;Wilcox et al, 2007). Most religious denominations disapprove of homosexuality and a broad coalition of religious groups has mobilized to oppose gay rights, including same-sex marriage (Campbell and Robinson, 2007).…”
Section: Religion and Homosexualitymentioning
confidence: 95%
“…Religious affiliation, Biblical literalism, and church attendance are strong predictors of intolerance toward gays and lesbians (Burdette et al, 2005;Finlay and Walther, 2003) and weaker support for gay rights, particularly same-sex marriage (Gaines and Garand, 2010;Olson et al, 2006;Wilcox et al, 2007). Most religious denominations disapprove of homosexuality and a broad coalition of religious groups has mobilized to oppose gay rights, including same-sex marriage (Campbell and Robinson, 2007).…”
Section: Religion and Homosexualitymentioning
confidence: 95%
“…This suggests that cultural issues may be playing a major role in sustaining the gender gap in political behavior and attitudes. Conversely, other studies have shown that gender does not have a strong effect on Americans' attitudes toward abortion (Barkan 2014;Cook, Jelen, and Wilcox 1992;Zigerell and Barker 2011) and same-sex marriage (Gaines and Garand 2010). Hence, although there are plausible reasons to think that gender could be a strong determinant of attitudes toward the religious exemption to the HHS mandate, the jury is still out.…”
Section: Determinants Of Attitudes On Social and Cultural Issuesmentioning
confidence: 95%
“…There is an extensive literature on the role of religion in shaping attitudes on social issues; however, as Jelen (2009) points out, which religion variables have an effect is subject to disagreement. Some scholars point to the effects of religious affiliation (Bolce and De Maio 1999;Brooks and Manza 2004;Kellstedt and Green 1993;Kellstedt et al 1997;Steensland et al 2000), whereas others focus their attention on religiosity and church attendance (Brooks and Manza 2004;Haider-Markel and Joslyn 2005;Sullins 1999) or values and beliefs (Brewer 2003a;2003b that the religion variables that may influence attitudes on social issues may not be the same that influence Americans' attitudes toward economic issues (Gaines and Garand 2010;McCarthy et al 2016;Wilson 2009). The bottom line is that there is a rich body of work connecting Americans' attitudes toward social issues and various religion variables.…”
Section: Determinants Of Attitudes On Social and Cultural Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Across the literature, gender, age, religious affiliation, religious intensity, education, income, marital status, ethnicity, and contact with gay people have all been suggested as significant sources of variation in attitudes on gay rights issues. In most studies, males, older respondents, Protestants, Catholics, those with greater church attendance, those with less education, lower-income respondents, African Americans, Latinos, married respondents, those from rural areas, Southerners, and those with limited contact with gays and lesbians all demonstrated lower support for same-sex marriage and were more likely to vote for bans (Barth, et al 2009;Baunach 2012;Becker 2012aBecker , 2012bBecker and Scheufele 2009;Brewer 2008;Brumbaugh, et al 2008;Burnett and Salka 2009;Dyck and Pearson-Merkowitz 2012;Egan and Sherrill, 2009;Fleischmann and Moyer 2009;Gaines and Garand 2010;Lewis and Gossett 2008;McKenzie and Rouse 2013;McVeigh and Diaz 2009;Olson et al 2006;Salka and Burnett 2012;Sherkat et al 2010;Sherkat et al 2011). Several of these studies report inconsistent results for some variables including gender, age, income, ethnicity, and marital status.…”
Section: Factors Influencing Opinion On Same-sex Marriagementioning
confidence: 99%